THE CURIOUS CASE OF THE CLOCKWORK MAN - Hodder, Mark, author 1962- (London : Snowbooks Ltd., 2011)
1862 : Albertian Britain is in the grip of conflicting forces. Engineers transform the landscape with bigger, faster, noisier and dirtier technological wonders; Eugenicists develop specialist animals to provide unpaid labour; Libertines oppose restrictive and unjust laws and flood the country with propaganda demanding a society based on beauty and creativity; while The Rakes push the boundaries of human behaviour to the limits with magic, sexuality, drugs and anarchy. "Sir Richard Francis Burton and poet Algernon Swinburne's investigation into a theft of black diamonds, ultimately embroiling them in the affairs of a dubious claimant, supposedly the heir of a cursed estate...is deliciously entertaining." -- Steampunk Scholar